2020
DOI: 10.1111/sum.12680
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide flux and soil carbon stock as affected by crop residue management and soil texture in semi‐arid maize croplands in Tanzania

Abstract: Crop residue management strategies must be adapted for improving carbon (C) balance and soil C stock in agroecosystems in sub‐Saharan Africa with consideration of the crop residue availability and site‐specific soil characteristics. We conducted field experiments to determine the effects of crop residue application method (incorporation/mulching) and quality (maize/cowpea) and N fertilizer application on the soil respiration rate and soil C stock in the surface soil layer (0–15 cm) in maize croplands with cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The use of crop residues as mulching materials or organic fertiliser can help to improve the soil organic carbon (SOC) and crop grain yield (Wang et al 2019). Nishigaki et al (2021) showed that the carbon storage after crop residue incorporation is not significant in a short time view but it increases with time. This is in accordance with Lu et al (2015) who found a significant increase in soil organic matter after 10 years of straw incorporation in the soil whereas the short-term effect was not significant.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The use of crop residues as mulching materials or organic fertiliser can help to improve the soil organic carbon (SOC) and crop grain yield (Wang et al 2019). Nishigaki et al (2021) showed that the carbon storage after crop residue incorporation is not significant in a short time view but it increases with time. This is in accordance with Lu et al (2015) who found a significant increase in soil organic matter after 10 years of straw incorporation in the soil whereas the short-term effect was not significant.…”
mentioning
confidence: 99%
“…The tillage practice (i.e. straw incorporation or mulching) represents an important factor in the decomposition process, as it affects the water regime within the soil and the contact area of residues and soil Nishigaki et al (2021).…”
mentioning
confidence: 99%
“…Recent studies suggest that 5–15% of this carbon pool is susceptible to decomposition during the thawing process triggered by global warming (Jansson & Hofmockel, 2020), which could lead to both CO 2 and CH 4 emissions. Soil management on a farm scale can affect both SOC level and CO 2 emissions, for example the incorporation of crop residue tends to increase CO 2 flux (Nishigaki et al., 2021). Soil constituents also play a critical role in regulating CO 2 and CH 4 emissions.…”
Section: Soil Management and Greenhouse Gas Emissionmentioning
confidence: 99%
“…Crop rotation and plant diversity in no‐tillage systems (NTS) can provide more favourable conditions for accumulating carbon (C) and nitrogen (N) in the soil profile (Alhameid et al, 2017; Eberhardt et al, 2021; Sant’Anna et al, 2017; Schmatz et al, 2017) and for nutrient cycling, increasing the productivity of agricultural systems by improving soil quality (Soares et al, 2019). Inclusion of legumes in crop rotations provides N to microorganisms that synthesize stable fractions of soil organic matter (SOM), in addition to promoting protection and stability of C, consequently reducing greenhouse gas (GHG) emissions (Nishigaki et al, 2021; Yao et al, 2019). The adoption of cover crops in cropping systems is recommended as a management strategy to increase soil C stocks (Chahal et al, 2020; Rosolem et al, 2016).…”
Section: Introductionmentioning
confidence: 99%